Effects of resisted sled towing on sprint kinematics in field-sport athletes - Lockie, R. G.; Murphy, A. J.; Spinks, C. D. (The Journal of Strength and Conditioning Research, 2003)
Weighted sled towing is a common resisted sprint training technique even though relatively little is known about the effects that such practice has on sprint kinematics. The purpose of this study was to explore the effects of sled towing on acceleration sprint kinematics in field-sport athletes. Twenty men completed a series of sprints without resistance and with loads equating to 12.6 and 32.2% of body mass. Stride length was significantly reduced by 10 and 24% for each load, respectively. Stride frequency also decreased, but not to the extent of stride length. In addition, sled towing increased ground contact time, trunk lean, and hip flexion. Upper-body results showed an increase in shoulder range of motion with added resistance. The heavier load generally resulted in a greater disruption to normal acceleration kinematics compared with the lighter load. The lighter load is likely best for use in a training program.